Computer aided assessment of mathematics - Sangwin, C. J. (Christopher J.) (Oxford University Press, 2013)
Computer aided assessment is rapidly becoming widely used in mathematics education from open access learning materials to interactive materials and online assessments. This book provides a survey of the field, theoretical background and practical examples. It is aimed at any teachers interested in using or developing their own online assessments.